2013
DOI: 10.1016/j.aca.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of differentially expressed saliva proteins in human immunodeficiency virus type 1 (HIV-1) infected individuals

Abstract: In the present study, we have established a new methodology to analyze saliva proteins from HIV-1-seropositive patients before highly active antiretroviral therapy (HAART) and seronegative controls. A total of 593 and 601 proteins were identified in the pooled saliva samples from 5 HIV-1 subjects and 5 controls, respectively. Forty-one proteins were found to be differentially expressed. Bioinformatic analysis of differentially expressed salivary proteins showed an increase of antimicrobial proteins and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Expression levels of members of the calcium-binding S100 protein family and "deleted in malignant brain tumours 1 protein" were up-regulated, while that of mucin 5B was down-regulated in HIV-1 seropositive saliva samples, suggesting new perspectives for monitoring HIV-infection and understanding the mechanism of HIV-1 infectivity 47 . Since whole saliva contains variegate microflora, several platforms were recently developed to investigate the human salivary metaproteome.…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…Expression levels of members of the calcium-binding S100 protein family and "deleted in malignant brain tumours 1 protein" were up-regulated, while that of mucin 5B was down-regulated in HIV-1 seropositive saliva samples, suggesting new perspectives for monitoring HIV-infection and understanding the mechanism of HIV-1 infectivity 47 . Since whole saliva contains variegate microflora, several platforms were recently developed to investigate the human salivary metaproteome.…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…Cystatin D is a member of cystatin family II, which is from the cystatin superfamily . It was demonstrated that CST5 expressed lowly in patients with bladder cancer and human immunodeficiency virus type 1 (HIV‐1) . Also, a previous study has proved that CST5 can inhibit xenograft tumour growth in vivo through restraining the Wnt/β‐catenin pathway .…”
Section: Introductionmentioning
confidence: 99%
“…7 It was demonstrated that CST5 expressed lowly in patients with bladder cancer and human immunodeficiency virus type 1 (HIV-1). 8,9 Also, a previous study has proved that CST5 can inhibit xenograft tumour growth in vivo through restraining the Wnt/β-catenin pathway. 10 Interestingly, CST5, encoding cystatin D, is induced by the vitamin D receptor (VDR) directly, which is reported to work as a tumour suppressor.…”
mentioning
confidence: 99%
“…Studies based on the quantitative analysis of saliva have been done to search for new ways to monitor the progression of the disease and to understand the mechanism of infection [19]. HIV neurocognitive disorders (HAND) have also been investigated with saliva for the possible involvement of the gut in the pathophysiological mechanisms through quantitative proteomics analysis of the saliva.…”
Section: Salivamentioning
confidence: 99%